Pendampingan Pelayanan Prima Di Klinik Shinta Medika - Trio Saputra; Eka, Eka; Wasiah Sufi (Jurnal Pengabdian UntukMu NegeRI, 2023)
The partner who is the target of the community service program is the Shinta Medika Clinic. Based on the results of observations and interviews, there are 3 main problems faced by partners including: (1) employees are not yet friendly to patients (2) the appearance of employees in providing services has not been noticed (3) service time does not yet have standards in providing services. Based on the above problems, solutions are offered (1) Assistance in providing services to patients (2) Assistance in employee performance in supporting services (3) Assistance in improving service standards. This program activity uses training and mentoring methods. The results of this service activity (1) Increasing employee knowledge in providing excellent service to patients, (2) Increasing knowledge in appearance to provide excellent service and (3) Maintaining service standards at the Shinta Medika clinic